Effect of salt addition on sous vide cooked whole beef muscles from Argentina - Vaudagna, Sergio Ramon; Pazos, Adriana Alejandra; Guidi, Silvina Mabel; Sanchez, Guillermo; Carp, D.J.; Gonzalez, Claudia Beatriz (Elsevier, 2019)
Sodium chloride (NaCl, 0–1.4%) and sodium tripolyphosphate (STPP, 0–0.5%) were added to Semitendinosus muscles and submitted to sous vide cooking at different temperatures (55–75 °C). The effects of these three factors on pH, cooking loss, instrumental colour parameters, protein solubilization and distribution, and micro- and ultra-structure were evaluated. Quadratic surface responses equations were obtained from data (pH, cooking loss and colour parameters) as a function of the salts concentrations and cooking temperature. Both salts – alone or in combination – successfully reduced cooking loss. The best results were obtained for the combinations 0.25%STPP + 1.20%NaCl and 0.25%STPP + 0.70%NaCl, and temperatures between 60 and 65 °C. Under these conditions, cooking loss was reduced close to 0%. pH was only dependent on STPP concentration, with a threshold concentration value of 0.25%. Temperature increment and NaCl addition produced a redness reduction. STPP incorporation recovered partially this parameter in comparison to non-added samples. Microscopy and SDS–PAGE results support the effect of the selected combinations of factors, suggesting that both salts together induced protein solubilization and gelation upon heating.